2021
DOI: 10.3390/ma14030621
|View full text |Cite
|
Sign up to set email alerts
|

Refractory CrMoNbWV High-Entropy Alloy Manufactured by Mechanical Alloying and Spark Plasma Sintering: Evolution of Microstructure and Properties

Abstract: In this study, bulk samples of a CrMoNbWV high-entropy alloy (HEA) were obtained for the first time by spark plasma sintering (SPS) of mechanically alloyed (MA) powders at 1200 °C, 1300 °C, and 1400 °C. Microstructure evolution, phase formation as well as wear and corrosion behavior were investigated. The MA powders’ phase composition was found to be represented by body-centered-cubic (BCC) solid solution. The solid solution partially decomposed to Laves phases under the sintering, such as Cr2Nb and (Fe, Cr)Nb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…The contents of the four elements are close to the initial design composition. Accordingly, the density of the thin film can be calculated via the rules of mixtures, 5.67 g cm −3 , which presents the lower density among reported similar HEAs composition, as shown in Figure 2 b, including NbTiV 2 Zr [ 26 ], NbTiVZr [ 26 ], CrNbTiVZr [ 26 ], CrNbTiZr [ 26 ], AlMo 0.5 NbTa 0.5 TiVZr [ 27 ], Al 0.3 NbTa 0.8 Ti 1.4 V 0.2 Zr 1.3 [ 27 ], Al 0.4 Hf 0.6 NbTaTiVZr [ 27 ], CrMoNbWV [ 28 ], and WNbMoTaV HEAs [ 28 ]. To study the mechanical properties of the AlTiVNb HEA film, the load–depth curves derived from the nanoindentation are shown in Figure 2 c and the modulus and hardness of the film are presented in Figure 2 d. The curves show high repeatability, illustrating that the film is dense and uniform.…”
Section: Resultsmentioning
confidence: 95%
“…The contents of the four elements are close to the initial design composition. Accordingly, the density of the thin film can be calculated via the rules of mixtures, 5.67 g cm −3 , which presents the lower density among reported similar HEAs composition, as shown in Figure 2 b, including NbTiV 2 Zr [ 26 ], NbTiVZr [ 26 ], CrNbTiVZr [ 26 ], CrNbTiZr [ 26 ], AlMo 0.5 NbTa 0.5 TiVZr [ 27 ], Al 0.3 NbTa 0.8 Ti 1.4 V 0.2 Zr 1.3 [ 27 ], Al 0.4 Hf 0.6 NbTaTiVZr [ 27 ], CrMoNbWV [ 28 ], and WNbMoTaV HEAs [ 28 ]. To study the mechanical properties of the AlTiVNb HEA film, the load–depth curves derived from the nanoindentation are shown in Figure 2 c and the modulus and hardness of the film are presented in Figure 2 d. The curves show high repeatability, illustrating that the film is dense and uniform.…”
Section: Resultsmentioning
confidence: 95%
“…Recent reports in the field have shown that the RHEAs produced by combined use of MA and SPS display advantageous mechanical properties (especially in strength and ductility) as compared to the alloys fabricated by arc melting [17,[23][24][25]. For instance, a WNbMoTaV RHEA with an average grain size of 5.3 µm and homogenous microstructures was fabricated by using MA and subsequent SPS consolidation [23].…”
Section: Introductionmentioning
confidence: 99%
“…Refractory CrMoNbTiW HEA synthesized [24] by mechanical alloying for 10 h followed by SPS consolidation has shown a high hardness (8.9 GPa) caused by the presence of residual the elements along with contaminations from milling bodies.…”
Section: Introductionmentioning
confidence: 99%
“…Metals that form monocarbides with a cubic structure such as NaCl, where metals are most likely have a common cationic sublattice with the face-centred cubic (fcc) sublattice, and carbon C is located in the anionic fcc sublattice [11]. Our previous work evaluated the effect of surface carbon saturation of the CrNbMoWV alloy on hardness, corrosion, and tribological properties [12].…”
Section: Introductionmentioning
confidence: 99%